EVALUASI SMILE DALAM PENGELOLAAN DATA DAN INFORMASI ( STUDI KASUS BPJS KETENAGAKERJAAN CAB.TANJUNG MORAWA) - Nurul Ifkah Lolona Silalahi (Bigint Computing Journal, 2024)
This study aims to evaluate SMILE at BPJS Ketenagakerjaan Tanjung Morawa Branch using the User Compatibility method which assesses the extent to which the application meets the needs, capabilities, and expectations of users.  This research method involves surveying SMILE users at BPJS Ketenagakerjaan Tanjung Morawa Branch by considering aspects of usability, efficiency, and user satisfaction. Data collection was carried out through questionnaires, interviews, and direct observation of SMILE users at BPJS Ketenagakerjaan Tanjung Morawa. The evaluation results show that SMILE Data and Information Management BPJS Ketenagakerjaan Tanjung Morawa Branch has a high level of user compatibility. Because it shows that all EUCS (End User Computing Satisfaction) independent variables consisting of Content, Format, Accuracy, Timeliness, Ease of Use have a significant relationship with SMILE user satisfaction. The resulting evaluation results and recommendations can serve as guidelines for future development and improvement.